2016
DOI: 10.1111/cas.12891
|View full text |Cite
|
Sign up to set email alerts
|

Elevated hepatocyte growth factor expression as an autocrine c‐Met activation mechanism in acquired resistance to sorafenib in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and the third leading cause of cancer‐related deaths worldwide. Limitations in HCC treatment result due to poor prognosis and resistance against traditional radiotherapy and chemotherapies. The multikinase inhibitor sorafenib is the only FDA approved drug available for advanced HCC patients, and development of second‐line treatment options for patients who cannot tolerate or develop resistance to sorafenib is an urgent medical need.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 59 publications
6
101
0
Order By: Relevance
“…Compensatory activation of growth factor signaling including EGF‐, insulin‐like growth factor‐, fibroblast growth factor‐, or hepatocyte growth factor signaling was described as a mechanism of HCC to adapt to sorafenib treatment . In line, our results corroborated compensatory activation of growth factor receptor signaling by sorafenib.…”
Section: Resultssupporting
confidence: 85%
“…Compensatory activation of growth factor signaling including EGF‐, insulin‐like growth factor‐, fibroblast growth factor‐, or hepatocyte growth factor signaling was described as a mechanism of HCC to adapt to sorafenib treatment . In line, our results corroborated compensatory activation of growth factor receptor signaling by sorafenib.…”
Section: Resultssupporting
confidence: 85%
“…Firtina Karagonlar et al . reported that SU11274 reversed the increased migration and invasion ability of sorafenib-resistant hepatocellular carcinoma cells37. In ovarian cancer, in vitro study, demonstrated that SU11274 reduced cell growth, motility, and invasive activity of EOC cells16.…”
Section: Discussionmentioning
confidence: 99%
“…MET pathway activation and dysregulation have been implicated in multiple cancers, including hepatocellular carcinoma (HCC) [1, 2], and may play a role in resistance to antiangiogenic therapy [3–6]. Similarly, increased expression of the receptor tyrosine kinase AXL has also been reported in HCC and may promote invasive behavior [7].…”
Section: Introductionmentioning
confidence: 99%